The Endo-α(1,4) Specific Fucoidanase Fhf2 From Formosa haliotis Releases Highly Sulfated Fucoidan Oligosaccharides - Trang, Vo Thi Dieu; Mikkelsen, Maria Dalgaard; Vuillemin, Marlene; Meier, Sebastian; Cao, Hang Thi Thuy; Muschiol, Jan; Perna, Valentina; Nguyen, Thuan Thi; Tran, Vy Ha Nguyen; Holck, Jesper; Van, Tran Thi Thanh; Khanh, Huynh Hoang Nhu; et al. (Frontiers in Plant Science, 2022)
Fucoidanases are endo-fucoidanases (also known as endo-fucanases) that catalyze hydrolysis of α-glycosidic linkages in fucoidans, a family of sulfated fucose-rich polysaccharides primarily found in the cell walls of brown seaweeds. Fucoidanases are promising tools for producing bio-active fucoidan oligosaccharides for a range of biomedical applications. High sulfation degree has been linked to high bioactivity of fucoidans. In this study, a novel fucoidanase, Fhf2, was identified in the genome of the aerobic, Gram-negative marine bacterium Formosa haliotis. Fhf2 was found to share sequence similarity to known endo-α(1,4)-fucoidanases (EC 3.2.1.212) from glycoside hydrolase family 107. A C-terminal deletion mutant Fhf2∆484, devoid of 484 amino acids at the C-terminus, with a molecular weight of approximately 46 kDa, was constructed and found to be more stable than the full-length Fhf2 protein. Fhf2∆484 showed endo-fucoidanase activity on fucoidans from different seaweed species including Fucus evanescens, Fucus vesiculosus, Sargassum mcclurei, and Sargassum polycystum. The highest activity was observed on fucoidan from F. evanescens. The Fhf2∆484 enzyme was active at 20-45°C and at pH 6-9, and had optimal activity at 37°C and pH 8. Additionally, Fhf2∆484 was found to be calcium dependent. NMR analysis showed that Fhf2∆484 catalyzed hydrolysis of α(1,4) linkages between L-fucosyl moieties sulfated on C2 (similar to Fhf1 from Formosa haliotis), but Fhf2∆484 in addition released oligosaccharides containing a substantial amount of 2,4-disulfated fucose residues. The data thus suggest that the Fhf2∆484 enzyme could be a valuable candidate for producing highly sulfated oligosaccharides applicable for fucoidan bioactivity investigations.